ANALYZING THE INFLUENCE OF LEADERSHIP STYLE TOWARD EMPLOYEE PERFORMANCE IN MAJESTIC EVENT ORGANIZER - Ediwan, Meilia; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2018)
Abstract. One of the factors that influence employee performance is leadership style that is applied by the leader in its company. This research is conducted in Majestic Event Organizer. The employees feel dissatisfaction toward the authoritarian leadership style that has being implemented by the superior, thus their performance tend to be declining and below the standard. This research is conducted to identify the influence of transformational, transactional, authoritarian and laissez-faire leadership style towards the employee performance whether the influence is positive or negative. To collect the data, the researcher used quantitative approach by utilizing online questionnaire to 35 members. The next step is the researcher analyzed the data by Multiple Linear Regression. The result of this study support the hypothesis where the transformational, transactional and laissez-faire leadership has positive influence towards the employee performance. Meanwhile, authoritarian leadership has a negative influence towards the employee performance. However, the transactional and laissez-faire leadership have insignificant influence toward the employee performance while the transformational and authoritarian leadership have significant influence toward employee performance. This study gives recommendation to the superior to implement transformational leadership style based on the finding that transformational leadership able to give positive and significant influence for the employee performance.Keywords: Authoritarian Leadership Style, Employee Performance, Laissez-faire Leadership Style, Transactional Leadership Style, Transformational Leadership StyleÂ